ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN PEMECAHAN MASALAH MATEMATIK SERTA KEMANDIRIAN BELAJAR DENGAN PENDEKATAN PROBLEM BASED LEARNIG PADA SISWA SMP - Annisa Nursyifa; Yulia Purnama; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study was aims to analyze critical thinking skills and mathematical problem solving in junior high school students with a Problem Based Learning approach in the matter of straight line equations. This study was conducted in class VIII F consisting of 36 students at CILILIN 1 Public High School. The method used in this study is descriptive qualitative. The instrument used is a description test instrument. The results of this study indicate that critical thinking skills and mathematical problem solving and the independence of students in class VIII F taught with the PBL approach are still relatively low. Factors that cause these conditions include students who do not understand the strategies in solving problems and in the ability to think critically students are not careful in answering questions and are not complete in the steps to answer the questions